Correction: Zhang et al. Multi-Source Information Monitoring Test of Fractured Rock Mass Destruction Characteristics and Sensitivity Analysis of Precursor Phenomena. Energies 2022, 15, 538 - Zhang, Qinghe; Zheng, Tianle; Wang, Xiaorui; Fang, Zhiyuan (Energies (Basel), 2025)
In the original publication [...]